Comprehensive Genomic Profiling of Anaplastic Thyroid Cancer Identifies Alterations in THRA, a Potential Modifier of Cellular Plasticity - Vaishakhi Trivedi; Vanita Noronha; Munita Bal; Pratik Chandrani; Disha Poojary; Elveera Saldanha; Anuradha Choughule; Priyanka Pange; Vinod Gupta; Nandini Menon; Vijay Patil; Minit Shah; et al. (JCO Global Oncology)
PURPOSELineage-specific cellular plasticity is one of the emerging hallmarks of cancer. The undifferentiated state of anaplastic thyroid cancer (ATC) represents an instance of cellular plasticity where lineage-specific molecular markers are underacknowledged. In this study, we identified recurrent mutations in the thyroid hormone receptor α (THRA) gene, which may play a role in lineage-specific cellular plasticity in ATC.MATERIALS AND METHODSWe performed whole-exome sequencing and targeted sequencing of 68 formalin-fixed paraffin-embedded orphan tumors of ATC from Indian patients.RESULTSOur analysis reveals the hallmark mutations in TP53 (approximately 42%), BRAF (approximately 10.3%), KRAS (approximately 2.9%), NRAS (29.4%), HRAS (23.5%), NF1 (1.5%), AKT1 (approximately 2.9%), and PIK3CA (approximately 1.5%) genes. Interestingly, we found significant mutations in THRA (approximately 11%) in our cohort, unlike the White population, which is a substantial gene in the thyroid cell's differentiation process. THRA mutations co-occur with TP53 and other hallmark genes, which suggests a synergetic molecular mechanism in phenotypic change in ATC.CONCLUSIONOur data reveal the significant association of THRA mutations potentially influencing cellular plasticity in a subset of patients with ATC.